Effects of Different Packaging on Quality of Indica-Japonica Hybrid Rice and Cooked Rice - ZHU Lin; TONG Li-tao; HE Yue; LIN Xu-dong; LING Jian-gang (Liang you shipin ke-ji, 2022)
In order to clarify the quality change of indica-japonica hybrid rice in different packaging，this experiment was conducted to study the effects of four packaging, woven bags, PE bags, vacuum packages and kraft paper bags, on the rice and steamed rice quality at room temperature (20~25 ℃) with YongYu 15 rice as raw material. The results showed that, with the extension of storage time, the fatty acid value, amylose content and rice hardness of indica japonica hybrid rice increased gradually, while the indexes of rice freshness value, taste value, viscosity and taste value of rice decreased gradually. The correlation between the quality indexes was significant (P<0.01). The results were evaluated by factor analysis and verified by sensory evaluation, the storage effects of the four kinds of packaging was as follows: Vacuum > PE bag > woven bag > kraft paper bag. The above results show that, the vacuum and barrier packaging could effectively delay the decrease of the quality of indica-japonica hybrid rice and its cooked rice, and improve its storage quality.